Overabundant wild ungulate populations in Europe: management with consideration of socio‐ecological consequences - Valente, Ana M.; Acevedo, Pelayo; Figueiredo, Ana M.; Fonseca, Carlos; Torres, Rita T. (Mammal review, 2020)
Throughout recent years, ungulates have experienced significant increases in numbers and geographic range sizes in Europe, becoming locally overabundant populations in some regions. Changes in legislation regarding poaching, abandonment of land and re‐naturalisation of habitats, and decreasing numbers of hunters, among other things, have led to alarming scenarios in wild ungulate biology. Although ungulates bring some financial benefits for ecosystems and society through tourism and hunting, the problems associated with populations that are no longer controlled can outweigh the advantages. Damage to forestry and agriculture, ungulate‐vehicle collisions, and diseases are among the most concerning problems related to ungulate overabundance. To deal with these problems and to decide on the best management strategy to apply, it is essential to have tools available to monitor populations with an integrative approach based on ecological change indicators, and to assess population and ecosystem status. Furthermore, in a globalised world, people’s opinions matter, and sociological studies regarding human perception of wild mammals must take place in order to allow proper management, including consideration of people’s expectations as well as animal and ecosystem needs. Successful and unsuccessful management strategies have already been attempted, and the knowledge of consequences over time enables an adaptive approach. Management of ungulate populations is a complex subject, and each case should be studied, analysing the cost_performance balance of measures to be taken, and ensuring ongoing financial means to carry out and continue with successful ecosystem management strategies. Multidisciplinary teams should be built, including biologists, veterinarians, stakeholders, sociologists, and others, to deal with the management of European wild ungulate populations. Ungulates such as red deer and wild boar have been increasing in the past decades in Europe, and so have their consequences. Damage to agriculture and forestry, emerging infectious diseases, and increasing ungulate‐vehicle collisions are only some of the consequences of ungulate populations that are no longer controlled. Ungulate expansion also increases conflicts among humans, and the study of these interactions should be integrated in an holistic perspective of ecosystems. This review gives researchers and the general public a brief summary of the situation of ungulates in Europe, suggests a novel socio‐ecological approach, and provides recommendations for stakeholders on how to deal with this situation, which is likely to intensify in the future.